THE ROLE OF FINANCIAL LITERACY AND EMPLOYEE COMPETENCE IN BUDGET MANAGEMENT EFFICIENCY: AN EMPIRICAL STUDY ON PRIVATE HIGHER EDUCATION INSTITUTIONS IN INDONESIA - Iman Supratman; Dewi Kurniasari; Dewi Sinta; Aliyyu Aziiza Rochmana; Lilis Sulastri (UIN Sunan Gunung Djati Bandung, 2025)
This study investigates the influence of financial literacy and employee competence on budget management efficiency in private higher education institutions in Indonesia. The research employs a quantitative approach with a survey of 120 administrative and financial staff across 15 institutions. Data were analyzed using multiple regression analysis. The results indicate that both financial literacy and employee competence have a significant positive effect on budget management efficiency. These findings suggest that enhancing employees’ financial knowledge and professional skills can substantially improve financial management practices in higher education institutions. Implications for human resource development and financial policy are discussed. The efficiency of budget management is a critical factor determining the operational and strategic success of higher education institutions (HEIs), particularly in the private sector where financial resources are often constrained. This study explores the impact of financial literacy and employee competence on the efficiency of budget management in private HEIs in Indonesia. Drawing on a survey of 120 financial and administrative staff across 15 institutions, this research employs multiple regression analysis to examine the relationships between the variables. Results reveal that financial literacy significantly enhances employees’ ability to plan, monitor, and control budgets, while employee competence including knowledge, skills, and problem-solving abilitiesalso plays a vital role in achieving efficient budget management. The findings underscore the importance of integrating human resource development initiatives with financial management strategies to improve institutional performance. These results contribute to the growing body of knowledge on the interrelation between financial management and human resource competence in higher education, providing practical guidance for policy and managerial decisions.